Co lze postavit v největším vnitrobloku města Brna? - Čapková, Eliška (Vysoké učení technické v Brně. Fakulta architektury)
bydlení ve městě je často hlučné, však ve vnitrobloku je tiché. Bydlení v zeleni blízko centra je vhodné jak pro rodiny s dětmi, tak pro starší obavytele.

Living in the city is very noisy, but there is place which is quiet. There is place in the green situated. the place is surrounded old parks and it is suitable for young family with children, also for old people.
What can be built in the largest city block in Brno?
Keywords: Bydlení ve městě; bydlení v zeleni; bydlení ve starém městě; Livindg in the city; living in the green; living in the old city